Experimental investigation of aluminum fins on relative thermal performance of sintered copper wicked and grooved heat pipes. (October 2022) - Khalid, Saif Ullah; Hasnain, Saqib; Ali, Hafiz Muhammad; Bano, Shehar; Nasir, Muhammad Ali; Abbas, Naseem
Abstract: Heat pipes are one of the most modern thermal devices used for high heat flux applications like fuel engines and thermal boilers to hydrogen storage tanks etc. Various kinds of thermal performance enhancement techniques have been employed to increase heat transfer through these pipes. For this purpose, manufacturing of a finned heat pipe is one of the famous techniques which maximizes heat transfer and increases operating range of heat pipes too. This study compiles the experimental results; 1) of installing Aluminum fins on the condenser section of heat pipes, 2) and a comparison between finned and finless distilled water based sintered wicked as well as grooved heat pipes, by keeping all other parameters same. The distribution of surface temperatures, thermal conductivity and thermal resistance is considered for comparison purposes. It is clearly observed that power surface temperature has an inverse relationship with the evaporator thermal resistance that is; if the power surface temperatures increases then the evaporator thermal resistance decreases. Also, installation of fins is more significant in sintered heat pipes as compared to grooved heat pipes. Due to installation of fins, there is an increase in the operating range which was observed 47% for sintered heat pipes and 30.1% for grooved heat pipes, when compared at 20 W. It has also been noted that the thermal conductivity of sintered heat pipes increased up to 73.2% due to the installation of fins and unexpectedly decreased up to 58.8% in case of grooved heat pipes. Thermal resistance of finned sintered heat pipes was 42% lower than finless type, and surprisingly it has increased up to 1.43 times in grooved heat pipes. Finally, a through comparison of finless sintered and grooved heat pipes results that finless grooved heat pipe shows the best performance and up to a 4.7% lower evaporator surface temperature was observed.